Prevention and Resolution of Sovereign Debt Crises - Ams, Julianne (Selected Legal and Institutional Papers Series; Selected Legal and Institutional Paper ;, 2018)
'The IMF's Role in the Prevention and Resolution of Sovereign Debt Crises' provides a guided narrative to the IMF's policy papers on sovereign debt produced over the last 40 years. The papers are divided into chapters, tracking four historical phases: the 1980s debt crisis; the Mexican crisis and the design of policies to ensure adequate private sector involvement ('creditor bail-in'); the Argentine crisis and the search for a durable crisis resolution framework; and finally, the global financial crisis, the Eurozone crisis, and their aftermaths.